Phylogenetic trophic specialization: a robust comparison of herbivorous guilds - Jorge, Leonardo R; Novotny, Vojtech; Segar, Simon T; Weiblen, George D; Miller, Scott E; Basset, Yves; Lewinsohn, Thomas M (Oecologia, 2017)
Resource specialization is a key concept in ecology, but it is unexpectedly difficult to parameterize. Differences in resource availability, sampling effort and abundances preclude comparisons of incompletely sampled biotic interaction webs. Here, we extend the distance-based specialization index (DSI) that measures trophic specialization by taking resource phylogenetic relatedness and availability into account into a rescaled version, DSI*. It is a versatile metric of specialization that expands considerably the scope and applicability, hence the usefulness, of DSI. The new metric also accounts for differences in abundance and sampling effort of consumers, which enables robust comparisons among distinct guilds of consumers. It also provides an abundance threshold for the reliability of the metric for rare species, a very desirable property given the difficulty of assessing any aspect of rare species accurately. We apply DSI* to an extensive dataset on interactions between insect herbivores from four folivorous guilds and their host plants in Papua New Guinean rainforests. We demonstrate that DSI*, contrary to the original DSI, is largely independent of sample size and weakly and non-linearly related with several host specificity measures that do not adjust for plant phylogeny. Thus, DSI* provides further insights into host specificity patterns; moreover, it is robust to the number and phylogenetic diversity of plant species selected to be sampled for herbivores. DSI* can be used for a broad range of comparisons of distinct feeding guilds, geographical locations and ecological conditions. This is a key advance in elucidating the interaction structure and evolution of highly diversified systems.
Keywords: Statistical comparability; Animals; Food Chain; Herbivory; Reproducibility of Results; Nutritional Status; rostliny; nutriční stav; Phylogeny; reprodukovatelnost výsledků; Distance-based specialization index (DSI*); hmyz; Plants; Host plant range; býložravci; zvířata; potravní řetězec; fylogeneze; Papua New Guinea; Insecta